Strategies Used by Lecturers in Teaching English Productive Skills at English Study Program of FKIP UIR: Strategies Used By Lecturers in Teaching English Productive Skill at English Study Program of FKIP UIR - Muhammad Ilyas (UIR Press, 2017)
Teaching English productive skills was considered to become the most difficult lesson, the students needed to have good pronunciation, master structure, discourse and the social context of cultural competence. Besides, speaking and writing were difficult, more effort was required on the part of the students and lecturers. It was not enough for the students to listen only. This research tried to explore the strategies used by the lecturers and their influences in developing students’ cognitive academic language proficiency by working on students’ English productive skills. This research was a descriptive qualitative research. It consisted of only one variable, which the researcher wanted to explore the description of strategies used by the lecturers and their influences on students’ English productive skills at English study program of FKIP UIR. In this research, researcher only focused on exploring the strategies used by the lecturers and describing the influences from those strategies on students’ English productive skills. The result of this research showed that there were some strategies used by lecturers in teaching English productive skills at English study program of FKIP UIR, they were: (1) in the speaking classroom; Buzz group, think-pair-share, circle of voices, video recording method. (2) in the Writing classroom; collaborative writing technique. All of those strategies were suitable for teaching speaking or writing and gave description for reader to increase students’ English productive skills.